2022
DOI: 10.1186/s12886-022-02679-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and visual outcomes of fovea-sparing internal limiting membrane peeling with or without inverted flap technique for myopic foveoschisis

Abstract: Background Vitrectomy and peeling of the internal limiting membrane (ILM) was an effective therapeutic approach for myopic foveoschisis with progressive visual loss. This study investigated the anatomical and visual outcomes of fovea-sparing ILM peeling with or without the inverted flap technique for patients with symptomatic myopic foveoschisis (MF). Methods We retrospectively reviewed the clinical data of patients with MF. Vitrectomy with fovea-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Zheng et al, who compared fovea sparing ILM surgery with and without the inverted flap, reported two cases of postoperative MH, one for each type of surgery. However, the MH in the non-inverted flap group required further surgery, whereas the inverted flap MH spontaneously closed at four months, presumably due to the presence of the flap 15 . More recently, Feng et al compared standard and fovea-sparing ILM peeling with combined FSIF ILM peeling in eyes with MF and lamellar hole and found a lower risk of post-operative MH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zheng et al, who compared fovea sparing ILM surgery with and without the inverted flap, reported two cases of postoperative MH, one for each type of surgery. However, the MH in the non-inverted flap group required further surgery, whereas the inverted flap MH spontaneously closed at four months, presumably due to the presence of the flap 15 . More recently, Feng et al compared standard and fovea-sparing ILM peeling with combined FSIF ILM peeling in eyes with MF and lamellar hole and found a lower risk of post-operative MH.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the growing consensus favoring fovea-sparing ILM peeling, recent reports have hinted at the potential for further refinement. Some authors have suggested that, particularly in cases with very thin fovea, such as outer lamellar holes with foveal detachment, the limited mechanical force applied during fovea sparing could still damage the extremely fragile tissue 15 , 18 . As a response to this concern, the combination with the inverted flap technique, well-established for treating large or persistent idiopathic MH or myopic MH, has been proposed 14 , 15 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Yet, a recent study evaluated the FSIP with or without ILMF technique for myopic foveoschisis and found the occurrence of postoperative FTMH was similar. 25 One possible explanation is the different subjects. The proportion of LMH (100%) and FD (73%) in our study is much higher than that (70% and 34%) in the recent study, which may cause the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Given our interpretation of Fig. 3 and the small case number in the study by Zheng et al, [ 1 ] we think the conclusion made by them may require some modifications.…”
mentioning
confidence: 80%
“…We read with interest the article “Anatomical and visual outcomes of fovea‑sparing internal limiting membrane (ILM) peeling with or without inverted flap technique for myopic foveoschisis” by Zheng et al [ 1 ]. In this article, the authors compared two different surgical techniques for treating myopic foveoschisis, and found that fovea‑sparing ILM peeling, either with or without inverted flap, resulted in similar anatomical and visual outcomes.…”
mentioning
confidence: 99%